Comparison of Various Methods for Blunting the Hemodynamic Response to Skull Pin Insertion in Neurosurgical Patients: A Systematic Review - Lakhe, Prashant; Kutum, Chayanika; Panchariya, Piyush; B.C, Anil Kumar; Ghimire, Niraj; Begum, Uzma; Sabu, Nayana (Indian Journal of Neurosurgery, 2025)
The application of skull pins can induce tachycardia and hypertension, potentially leading to intracerebral hemorrhage or elevated intracranial pressure. Both pharmacologic and non-pharmacologic modalities have been employed to mitigate these deleterious effects, with varying degrees of success.We aimed to conduct a systematic review to assess and compare various strategies for preventing the hemodynamic response to skull pin insertion in neurosurgery.We searched the PubMed, Google Scholar, and Cochrane Library databases, along with forward and backward citations, up to May 2024. Randomized controlled trials investigating methods used to blunt the hemodynamic response to skull pin application in neurosurgical patients were included. A qualitative review was performed on the effects of local anesthesia (LA), comparisons between local and intravenous agents, as well as the use of α-agonists and opioids. The quality of evidence was assessed using the Risk of Bias-2 tool. This study is registered on PROSPERO (CRD42024485232).Of the 10,812 records identified, 54 studies were included, the majority of which had either low or some concerns regarding the risk of bias. In 45% of the studies, local infiltration alone was effective in preventing the hemodynamic response. Similarly, scalp block alone was effective in 92.3% of trials. Both clonidine and dexmedetomidine were found to be effective in most studies, whereas opioids were ineffective in 50% of the trials. When comparing LA with IV agents, 62.5% of studies reported that both methods were equally effective.Among methods evaluated, scalp block and dexmedetomidine (particularly at 1 µg/kg IV) consistently demonstrated high efficacy in blunting the hemodynamic response to skull pin insertion. Clonidine also showed robust effectiveness across studies. Local infiltration was beneficial in most, but not all cases, while opioids and β-blockers showed variable or limited efficacy.
Keywords: neurosurgery; hemodynamics; hypertension; tachycardia; skull pin